An assessment of differences in costs and health benefits of serology and NAT screening of donations for blood transfusion in different Western countries. Issue 6 (22nd June 2017) - Janssen, M. P.; van Hulst, M.; Custer, B.; ,
Abstract : Background and Objectives: The cost‐utility of safety interventions is becoming increasingly important as a driver of implementation decisions. The aim of this study was to compare the cost‐utility of different blood screening strategies in various settings, and to analyse the extent and cause of differences in health economic results. Materials and Methods: For eight Western countries (Australia, Canada, Denmark, Finland, France, The Netherlands, UK and the United States of America), data were collected on donor and recipient populations, blood products, screening tests, and on patient treatment practices and costs. An existing ISBT web‐tool model was used to assess the cost‐utility of various strategies for HIV, HCV and HBV screening. Results: The cost‐utility ratio of serology screening for these eight countries ranges between −11 000 and 92 000 US$ per QALY, and for NAT between −12 000 and 113 000 US$ per QALY when compared to no screening. Combined serology and NAT ranges between 600 and 217 000 US$ per QALY. The incremental cost‐utility of NAT after implementation of serology screening ranges from 2 231 000 to 15 778 000 US$ per QALY. Conclusion: There are substantial differences in costs per QALY between countries for various HIV, HBV and HCV screening strategies. These differences are primarily caused by costs of screening tests and infection rates in the donor population. Within each country, similar cost per QALY results for serology and NAT compared to no screening, coupled with evidence of limited value of serology and NAT together prompts the need for further discussion on the acceptability of parallel testing by serology and NAT.